Produção de sentidos na leitura de anúncios publicitários: perspectivas para o ensino - Almeida, Suseli Corumba dos Santos (2007)
This dissertation is included in the research line of Reading, Writing and Teaching and its theme is the reading of the advertising text in the cycle II of the Fundamental Teaching. By assuming that the teaching of reading should take in consideration the reader's previous knowledge in the establishment of the textual coherence, it is intended to evidence through the advertising announcements analysis transmitted in the print media, the importance of the previous knowledge in the construction of the senses, based in linguistic aspects, in the world knowledge and in the textual knowledge. For such work, studies related to the cognitive processes involved in the act of understanding and the establishment of the textual coherence (KOCK, 2003, 2004a, 2004b; KOCH & TRAVAGLIA, 1999, 2004; KOCH & ELIAS, 2006; VAN DIJK, 1977, 2002; FÁVERO, 1995; MARCUSCHI, 2004; GARRAFA, 1987); studies related to the textual gender (BAKHTIN, 1997; MARCUSCHI, 2002 and PINHEIRO, 2002) and studies related to the advertising textual gender (GONZALES, 2003; IASBECK, 2002; CARVALHO, 1996 and SANDMANN, 1993) were considered. The focus in advertising announcements is due to work of empiric observation, accomplished in the fourth grade of the cycle II of the Fundamental Teaching, whose results showed the students limits of the reading of that textual gender, although they are present in their daily lives. The results thus obtained in this work evidenced the importance of the previous knowledge in the production of senses of advertising texts, transmitted in the media printed. Therefore, the accomplished research brings contributions for the teaching of reading and opens perspectives for new investigations in the field